Covidfencing effects on cross-border deterritorialism: the case of Europe - Medeiros, E.; Guillermo Ramírez, M.; Ocskay, G.; Peyrony, J. (European Planning Studies, 2021)
The beginning of 2020 saw the global spreading of the COVID-19 pandemic, leading to a systematic closure of national borders across the world, which we refer to as the ‘covidfencing’ panorama. As expected, in Europe, where close to two million commuters cross national borders on a daily basis to work, this new reality has provoked significant setbacks to their lives. Based on evidence already available from several sources, this article presents some of the main impacts of the covidfencing process in the European cross-border (CB) areas. It does so by relating this process to the components of a proposed deterritorialism conceptual framework. In essence, it was possible to conclude that social related components like the sharing of health facilities and the need to work across borders show the existence of a high degree of deterritorialism in several parts of Europe. Nevertheless, more integration and deterritorialism is required everywhere, and simultaneously at the social, economic, physical and institutional levels. Crucially, covidfencing has highlighted the need for improving cross-border cooperation (CBC) with a view to mitigating persistent CB barriers and European integration processes.